Atomic rearrangement of a sputtered MoS2 film from amorphous to a 2D layered structure by electron beam irradiation - Bong Ho Kim (Nature Portfolio, 2017)
Abstract We synthesised a crystalline MoS2 film from as-sputtered amorphous film by applying an electron beam irradiation (EBI) process. A collimated electron beam (60 mm dia.) with an energy of 1 kV was irradiated for only 1 min to achieve crystallisation without an additional heating process. After the EBI process, we observed a two-dimensional layered structure of MoS2 about 4 nm thick and with a hexagonal atomic arrangement on the surface. A stoichiometric MoS2 film was confirmed to grow well on SiO2/Si substrates and include partial oxidation of Mo. In our experimental configuration, EBI on an atomically thin MoS2 layer stimulated the transformation from a thermodynamically unstable amorphous structure to a stable crystalline nature with a nanometer grain size. We employed a Monte Carlo simulation to calculate the penetration depth of electrons into the MoS2 film and investigated the atomic rearrangement of the amorphous MoS2 structure.